1978
DOI: 10.1128/jvi.26.2.221-225.1978
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of Streptococcus pneumoniae with bacteriophage DNA

Abstract: It was possible to transfect Streptococcus pneumoniae with DNA obtained from a newly isolated bacteriophage, diplophage-4 (Dp-4). Optimal frequency of transfection (0.9%) required the use of a nuclease-defective mutant; with wild-type bacteria, the transfection frequency was about 100-fold lower. Transfection requires physiological conditions that appear to be similar to the competent state needed for genetic transformation (A. Tomasz, J. Bacteriol. 91:1050--1061, 1966).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
(2 reference statements)
1
7
0
Order By: Relevance
“…The results shown in Table 1 demonstrate that the infectivity of Cp-1 DNA was remarkably reduced when the DNA was treated with proteolytic enzymes. In contrast, Dp-4 DNA was not affected by the treatment with proteases as previously reported (31). The fact that the inactivation could be prevented by the specific protease inhibitor indicated that we were analyzing an effect which must be attributed to specific protease activity and not, for example, to contaminating nucleases.…”
supporting
confidence: 74%
See 3 more Smart Citations
“…The results shown in Table 1 demonstrate that the infectivity of Cp-1 DNA was remarkably reduced when the DNA was treated with proteolytic enzymes. In contrast, Dp-4 DNA was not affected by the treatment with proteases as previously reported (31). The fact that the inactivation could be prevented by the specific protease inhibitor indicated that we were analyzing an effect which must be attributed to specific protease activity and not, for example, to contaminating nucleases.…”
supporting
confidence: 74%
“…Transfection with mature Dp-4 (30,31) and w3 phage DNAs as well as with the replicating form of w3 DNA has been reported in Streptococcus pneumoniae (11,26). In addition, a substantial t In memoriam of our friend Domingo Rodriguez.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is substantial knowledge on the transfection of several streptococcal species [1][2][3], the infection of lactic streptococci by purified bacteriophage DNA has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%